Effects of Donor x Inducer Interaction on the Success of Haploid Induction and Comparison of Haploid Seed Identification Methods in the In vivo Maternal Haploid Technique in Maize - Berk Vural; Umut Songur; Sezgin Kızık; Fatih Kahrıman; Abdullah Dişbudak (Journal of Agricultural Sciences)
This study was conducted to investigate the effect of donor and inducer lines on the haploid induction rate in the in vivo maternal doubled haploid technique in maize and to compare the methods used in haploid seed separation. In the study, three donor materials were used for induction crossing with two inducer lines. Seedling immersion and stem injection techniques were used as chromosome doubling methods. Eye separation, spectral measurements and image processing were used to identify seed classes. Data were modeled using support vector machine method and created models were evaluated over the complexity matrix. The results of the research revealed that the haploid induction rate varies depending on the donor genotypes and inducers, and the genotype responses against the applied chromosome doubling method were also different. Differences were observed in the success of the three methods compared for haploid and diploid seed separation. The successful classification rates were 87%, 83%, and 79% in visual, spectral and image processing models, respectively. Results showed that both spectral technique and image processing technique can be used to distinguish haploid/diploid seeds in in vivo maternal haploid technique.